PERAN PEMUDA DALAM MEMBANGUN CITRA PARIWISATA HALAL DI DESA SETANGGOR - Busaini Busaini; Baiq Handayani Rinuastuti; Feriyadin Feriyadin; Andrian Wijanarko; Khairul Amri Assidiq; Lalu Ardian Hadinata; Sintiar Rahmaningsih (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
The process of building the image of Halal tourism is inseparable from the participation of youth in providing Halal hospitality services to tourists based on Islamic values that are believed by the wider community as their local characteristics (authenticity). This study aims to reveal the role of youth in building the image of Halal tourism in terms of the perspective of producers (suppliers) or people who present local service products according to Islamic values that are believed to be. This study uses a qualitative descriptive phenomenology approach. Data obtained through observation and in-depth interviews with 5 tourism activists including 2 adult groups such as; Pokdarwis Chairperson, Pokdarwis treasurer, and 3 youth groups involved in the Sekartije pokdarwis management. The results show that young people who are members of Pokdarwis Sekartije Desa Setanggor as destination managers have started to have awareness to maintain and realize the image development of Halal tourist destinations by making it easier for tourists to get Halal tourism products and service facilities in Setanggor Village, which are supported by Halal habits (Halal practice) that have become the needs of the villagers.